2020
DOI: 10.1371/journal.pgen.1008546
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility established by Pou5f3, Sox19b and Nanog primes genes for activity during zebrafish genome activation

Abstract: In many organisms, early embryonic development is driven by maternally provided factors until the controlled onset of transcription during zygotic genome activation. The regulation of chromatin accessibility and its relationship to gene activity during this transition remain poorly understood. Here, we generated chromatin accessibility maps with ATAC-seq from genome activation until the onset of lineage specification. During this period, chromatin accessibility increases at regulatory elements. This increase i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 89 publications
(175 reference statements)
9
63
0
Order By: Relevance
“…S7a). We concluded that Sox19b binding contributes to establishment of chromatin accessibility during MZT, confirming the results of a previous study 13 .…”
Section: Resultssupporting
confidence: 92%
“…S7a). We concluded that Sox19b binding contributes to establishment of chromatin accessibility during MZT, confirming the results of a previous study 13 .…”
Section: Resultssupporting
confidence: 92%
“…Indeed, chromatin accessibility profiles of cell types executing similar functions can be highly similar despite showing different expression patterns and being controlled by different master TFs (Maurano et al, 2012;McKay and Lieb, 2013). Moreover, accessibility can signify priming of a locus for expression without commencing transcription (Lara-Astiaso et al, 2014;Pálfy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the question to answer remains: what is the mechanism which triggers miR-430 transcription and that of other minor wave transcribed genes? While the stem cell factors Pou5f3/Pou5f1, SoxB1/Sox19b and Nanog were previously shown to be required for miR-430 gene activation (Lee et al , 2013; Miao et al , 2020), they are unlikely to selectively regulate minor wave genome activation, as a large number of major wave genes also depend on these factors (Gao et al , 2020; Lee et al , 2013; Miao et al , 2020; Palfy et al , 2020; Veil et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…}. In addition, several molecular mechanisms have been suggested to regulate the timing of genome activation: i) delayed availability of pioneering transcription factors (Lee et al , 2013); ii) or that of the transcription initiation machinery (Bartfai et al , 2004; Ferg et al , 2007; Veenstra et al , 1999); iii) sequential increase in chromatin accessibility (Blythe and Wieschaus, 2016; Palfy et al , 2020); iv) gradual formation of transcriptionally competent chromatin (Lindeman et al , 2011; Chan et al , 2019); v) elongation of the cell cycle, permissive for elongating transcription (Blythe and Wieschaus, 2015; Collart et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation